2008
DOI: 10.1186/1471-2407-8-115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic analysis of hepatitis B virus infection in diffuse large B-cell lymphoma

Abstract: BackgroundHepatitis B virus (HBV) infection in diffuse large B-cell lymphoma (DLBCL) patients is a common complication in China. However, the clinical relevance of HBV infection with respect to DLBCL disease stages and patient survival remains unclear. The main objective of the current study was to analyze the clinical features and to evaluate the prognostic factors of HBV infection in DLBCL patients.MethodsIn this retrospective study, DLBCL patients were divided into two groups as HBsAg-positive (n = 81) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
7
55
1
Order By: Relevance
“…The present study demonstrated an earlier age of disease onset in the HBsAg-positive DLBCL patient group. These two facts suggest that HBV acts as an etiologic factor for DLBCL development, which is in agreement with the results of an earlier relevant study; however, an apparent correlation between HBsAg and prognosis was not revealed in the earlier study (23). The current study demonstrated that HBsAg-positive DLBCL patients had poorer OS rates compared with HBsAg-negative patients (62.2% HBsAg-positive vs. 76.2% HBsAg-negative, P=0.018; Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The present study demonstrated an earlier age of disease onset in the HBsAg-positive DLBCL patient group. These two facts suggest that HBV acts as an etiologic factor for DLBCL development, which is in agreement with the results of an earlier relevant study; however, an apparent correlation between HBsAg and prognosis was not revealed in the earlier study (23). The current study demonstrated that HBsAg-positive DLBCL patients had poorer OS rates compared with HBsAg-negative patients (62.2% HBsAg-positive vs. 76.2% HBsAg-negative, P=0.018; Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Although some autoimmune diseases show a clear tendency towards MALT lymphomas (such as Sjogren’s syndrome and Hashimoto’s thyroiditis), most of the lymphomas in SLE (as well as RA) are of the diffuse large B-cell type. As a caveat to this, there has been recent evidence suggesting that hepatitis B may play a role in the development of diffuse large B-cell lymphoma, in a Chinese general population sample(46). To date however, there is very little evidence of a strong role for infectious agents as mediators of lymphoma risk in SLE.…”
Section: Hematological Malignancies and Inflammationmentioning
confidence: 99%
“…Takai et al reported that, in 601 patients with hematological malignancies, the incidence of post-chemotherapy liver injury among patients with chronic HBV infection, i.e., HBV carriers, was significantly higher than that among non-carriers, suggesting that chronic hepatitis virus infection might interfere with chemotherapy and affect the outcomes of these patients 6. Another study that investigated chronic HBV infections in diffuse large B-cell lymphoma patients showed that the overall survival of carrier patients with hepatic dysfunction was significantly shorter than that of patients without liver dysfunction 7. In contrast, significant hepatic dysfunction and reactivation of the hepatitis C virus (HCV) are less common among HCV-infected patients treated with chemotherapy for hematological malignancies 3,8.…”
Section: Introductionmentioning
confidence: 99%